Influence Of Temperature, Relative Humidity And Interspecific Competition On The Population Growth Dynamics Of Three Pests Of Stored Product, Oryzaephilus Surinamensis (L.), Sitophilus Oryzae (L.) And Tribolium Castaneum (Herbst) - Goh , Xin Yu (2015)
Kesan suhu, kelembapan relatif dan persaingan interspesifik ke atas dinamik perkembangan populasi tiga perosak hasil simpanan, Oryzaephilus surinamensis (Linnaeus), Sitophilus oryzae (Linnaeus) dan Tribolium castaneum (Herbst) telah dikaji. Ketiga-tiga spesies ini dipelihara dalam linkungan julat suhu 26-40°C serta kelembapan relatif 7-85%. Anggaran suhu perkembangan optima bagi O. surinamensis, S. oryzae dan T. castaneum masing-masing adalah dalam lingkungan 29.61-33.96, 27.63-27.91 dan 29.92-33.53°C, tertakluk kepada kelembapan relatif. T. castaneum mempunyai suhu maut yang paling tinggi (40°C), disusuli oleh O. surinamensis (38°C) dan S. oryzae (36°C). S. oryzae tidak dapat hidup pada kelembapan relatif yang terlampau rendah (7%) di bawah semua suhu yang diuji. Kelembapan relatif yang tinggi secara umumnya memanfaatkan perkembangan populasi ketiga-tiga spesies ini. Dalam usaha untuk menerangkan reaksi ketiga-tiga spesies ini terhadap kelembapan relatif, kajian imbangan air telah dijalankan. The effects of temperature, relative humidity and interspecific competition on the population growth dynamics of three pests of stored product, Oryzaephilus surinamensis (Linnaeus), Sitophilus oryzae (Linnaeus) and Tribolium castaneum (Herbst) were investigated. These three species were reared under a range of temperatures (26-40°C) and relative humidities (RH) (7-85%). The estimated optimum growth temperature for O. surinamensis, S. oryzae and T. castaneum ranged from 29.61-33.96, 27.63-27.91 and 29.92-33.53°C, respectively, depending on RH. Lethal temperature of T. castaneum was the highest (40°C), followed by O. surinamensis (38°C) and S. oryzae (36°C). S. oryzae were unable to survive at extreme low RH (7%) at all temperatures tested. High RHs were generally beneficial to the population growth of all three species. In an attempt to elucidate the reaction of these species towards RH, water balance studies were carried out.